PENGARUH TINGKAT PERTUMBUHAN PENJUALAN DAN PERPUTARAN PIUTANG TERHADAP LIKUIDITAS PERUSAHAAN MANUFAKTUR - Arika, Nindya; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to find out the influence of growth level of sales and receivables turnover to the liquidity.This research has been conducted in manufacturing companies which are enganged in the field of automotiveand component which are listed in Indonesia Stock Exchange. The samples are 9 manufacturing companieswhich are enganged in the field of automotive and component which are listed in Indonesia Stock Exchange(IDX) and these manufacturing companies have been selected by using purposive sampling. The research datais the secondary data. The collected data has been analyzed by using classic assumption test before thehypothesis test is carried out. The hypothesis test has been conducted by using multiple linear regressions, t testand F test. The result of the analysis shows that the growth level of sales and receivables turnover has positiveand significant influence to the liquidity of manufacturing companies which are enganged in the field ofautomotive and component which are listed in Indonesia Stock Exchange.Keyword: Liquidity, receivable turnover, growth level of sales.